How to succeed at medical interviews. Issue 6 (July 2017) - Koshy, Kiron; Whitehurst, Katharine; Liu, Alison; Gundogan, Buket; Fowler, Alexander; Agha, Riaz
Abstract : Few people truly relish being interviewed. But as a professional, you will go through a number of interviews in your life that will affect your career progression. In this article, we provide some tips on how best to prepare for a medical interview, both in terms of your portfolio and interview practice. Advice is also given on how to maximize performance during the interview and gain the most from reflection afterwards.